2004
DOI: 10.1177/00222194040370050601
|View full text |Cite
|
Sign up to set email alerts
|

Naming Speed Deficits in Adults with Reading Disabilities

Abstract: The present study investigated the persistent nature of naming speed deficits within the context of the double-deficit hypothesis in a university sample of adults with reading disabilities (RD). Twenty-five university students with RD were compared to 28 typically achieving readers on measures of reading skill, phonological processing, and naming speed. The results indicated that both naming speed and phonological processing deficits characterized the RD group. In a regression analysis, neither naming speed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
2
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 40 publications
(108 reference statements)
8
29
2
5
Order By: Relevance
“…The association of phonology and rapid naming is equally strong with early reading speed in 1 st grade, but the association with rapid naming increases after the initial school years, while the associations with phonology stay at the same level until 8 th grade. This is in line with previous research reporting that rapid naming ability is relatively persistent until adulthood van den Bos, Zijlstra, & lutje Spelberg, 2002;Vukovic, Wilson, & Nash, 2004). It has also been shown that rapid naming plays a more significant role in more regular languages, like the highly transparent Finnish language, than in opaque languages like English (Bradley & Bryant, 1983;de Jong & van der Leij, 1999;Kirby, Georgiou, Martinussen, & Parrila, 2010;Wimmer, Landerl, & Schneider, 1994).…”
Section: Predicting Reading Until Adolescencesupporting
confidence: 91%
“…The association of phonology and rapid naming is equally strong with early reading speed in 1 st grade, but the association with rapid naming increases after the initial school years, while the associations with phonology stay at the same level until 8 th grade. This is in line with previous research reporting that rapid naming ability is relatively persistent until adulthood van den Bos, Zijlstra, & lutje Spelberg, 2002;Vukovic, Wilson, & Nash, 2004). It has also been shown that rapid naming plays a more significant role in more regular languages, like the highly transparent Finnish language, than in opaque languages like English (Bradley & Bryant, 1983;de Jong & van der Leij, 1999;Kirby, Georgiou, Martinussen, & Parrila, 2010;Wimmer, Landerl, & Schneider, 1994).…”
Section: Predicting Reading Until Adolescencesupporting
confidence: 91%
“…The phonological deficit hypothesis has been supported by numerous studies which have identified delays for the sensitivity to rhyme, alliteration, and phonemic segmentation during the development of reading (7)(8)(9) . However, studies (6,8) indicate the existence of deficits in addition to problems with phonological processing, such as deficits in working memory, in perceptual-motor automaticity and in rapid naming, which may be present not only in students with learning disabilities, but also in students who have some difficulty in learning the mechanism of phoneme-grapheme conversion during literacy.…”
Section: Introductionmentioning
confidence: 93%
“…RAN has also been found to predict reading disabilities at school age (e.g., and to differentiate children with a reading disability (RD) from controls without a RD O'Malley, Francis, Foorman, Fletcher, & Swank, 2002;. Differences between RD and control groups seem to occur also in adulthood (Vukovic, Wilson, & Nash, 2004).…”
Section: Yhteenveto (Finnish Summary) Nopea Nimeäminen Ja Lukemisen Smentioning
confidence: 99%